Madalena: The Entangled History of One Indigenous Floridian Woman in the Atlantic World. Issue 2 (20th March 2017) - Cave, Scott
Abstract : In 1549, after 11 years of slavery, and exile, an indigenous woman made it home to her people. In the time of her captivity, she became one of the most geopolitically important and well-traveled indigenous women in the Spanish Empire. Her name—or the name Spanish society gave her—was Madalena, and she returned home to Tocobaga, in what is now Tampa Bay. From bondage in Havana, she was taken to be the translator for a missionary expedition that sought to peacefully convert her people into citizens of the imagined Spanish colony of Florida. That mission, like every other European attempt to settle the region up to the nineteenth century, would fail, but this latest failure of Spanish colonialism meant that Madalena could return to life among her own people, unlike most indigenous slaves of the sixteenth century.